2009
DOI: 10.1016/j.neunet.2009.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine-modulated dynamic cell assemblies generated by the GABAergic striatal microcircuit

Abstract: The striatum, principal input structure of the basal ganglia, is crucial to both motor control and learning. It receives convergent input from all over neocortex, hippocampal formation, amygdala and thalamus, and is the primary recipient of dopamine in the brain. Within the striatum is a GABAergic microcircuit that acts upon these inputs, formed by the dominant medium-spiny projection neurons (MSNs) and fast-spiking interneurons (FSIs). There has been little progress in understanding the computations it perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
180
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(187 citation statements)
references
References 90 publications
7
180
0
Order By: Relevance
“…We have previously considered the intimate (monotonic) relationship between expected precision and expected utility in this context (see Friston et al, 2014, for a fuller discussion). The role of the neuromodulator dopamine in encoding precision is also consistent with its multiplicative effect in equation 2.7, to nuance the selection among competing policies (Fiorillo et al, 2003;Frank, Scheres, & Sherman, 2007;Humphries, Wood, & Gurney, 2009;Humphries, Khamassi, & Gurney, 2012;Solway & Botvinick, 2012;Mannella & Baldassarre, 2015). We will return to this later.…”
Section: Belief Updating and Belief Propagationmentioning
confidence: 71%
“…We have previously considered the intimate (monotonic) relationship between expected precision and expected utility in this context (see Friston et al, 2014, for a fuller discussion). The role of the neuromodulator dopamine in encoding precision is also consistent with its multiplicative effect in equation 2.7, to nuance the selection among competing policies (Fiorillo et al, 2003;Frank, Scheres, & Sherman, 2007;Humphries, Wood, & Gurney, 2009;Humphries, Khamassi, & Gurney, 2012;Solway & Botvinick, 2012;Mannella & Baldassarre, 2015). We will return to this later.…”
Section: Belief Updating and Belief Propagationmentioning
confidence: 71%
“…However, our results are in line with recent detailed modeling studies that have indicated unexpected, counter-intuitive properties of striatal microcircuits. In particular, the GABAergic input from FSIs seems not to greatly reduce overall MSN firing (Moyer and Wolf, 2009) and may even increase it (Humphries et al, 2009). FSIs are well placed to determine the fine timing of MSN spiking (Koos et al, 2004;Berke, 2009;Wilson, 2009) and may serve to control the correlations between members of MSN ensembles (Humphries et al, 2009) more than their gross firing rate.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the GABAergic input from FSIs seems not to greatly reduce overall MSN firing (Moyer and Wolf, 2009) and may even increase it (Humphries et al, 2009). FSIs are well placed to determine the fine timing of MSN spiking (Koos et al, 2004;Berke, 2009;Wilson, 2009) and may serve to control the correlations between members of MSN ensembles (Humphries et al, 2009) more than their gross firing rate. Another unanticipated property of FSIs is that, though coupled together by gap junctions, they do not normally show high synchrony (Berke, 2008;Hjorth et al, 2009;Humphries et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations